Rencana Program dan Kegiatan Pembelajaran Semester (RPKPS) Mata Kuliah Karya Tulis Ilmiah - Hidayatul Fikra; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to discuss the semester learning program and activity plan for the scientific paper course. This study uses a qualitative approach by applying a descriptive-analytical method. The results of the study and discussion show that the scientific paper course is designed based on graduate learning outcomes, course learning outcomes, sub-course learning outcomes, course descriptions, study materials, lecture time, learning resources, assessment and evaluation matrices for graduate learning outcomes, and assessment rubrics. This study concludes that the semester learning program and activity plan for the scientific paper course is in line with the Indonesian national qualification framework, graduate competency standards, graduate profiles, and learning outcomes of graduates of the Sufism and Psychotherapy study program.